Impact Of Social Media Advertising Exposure And Privacy Perceptions On Students' Attitudes - Azisah, Afiq; Aqsa, Muhammad; Rahmawati, Rahmawati (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to determine how exposure to social media advertising influences students' perceptions and attitudes toward privacy, and how these two factors are interrelated. Methodology: A quantitative approach was used through a questionnaire survey administered to 100 students in the Management Study Program at the University of Muhammadiyah Palopo. The variables analyzed include exposure to social media advertising, perceptions of privacy, and students' attitudes toward advertising on social media. Data were analyzed using statistical techniques with the support of the SmartPLS software. Results: The analysis revealed that exposure to social media advertising has a positive but statistically insignificant effect on students' attitudes. In contrast, perceptions of privacy were found to have a significant positive influence on students' attitudes. Findings: The study also identified a very strong relationship between advertising exposure and privacy perception, as reflected in an R-squared value of 0.865. This indicates that students' privacy perceptions act as a critical moderating factor in shaping attitudes toward social media advertising. Novelty: The research highlights the nuanced role of privacy perceptions in moderating advertising effects, an area that has been relatively underexplored in the context of student populations in Indonesian higher education. Originality: T his study contributes to the limited literature by empirically examining how privacy concerns interact with advertising exposure among university students in Indonesia, using SmartPLS as an analytical tool.. Conclusion: While direct exposure to social media advertising alone may not significantly influence student attitudes, students’ perceptions of privacy play a vital role in shaping their responses. Marketers and educators should therefore consider privacy concerns when designing digital advertising strategies. Type of Paper: Research Paper.